Factors Affecting Maternal Health Care Services Utilization in Nepal: Insight from the Nepal Demographic Health Survey 2006 and 2011 - Shrestha, Gauri (Nepalese Journal of Statistics, 2017)
Background: In this study, a maternal health care service is analyzed under the components of place of delivery (POD). POD is highlighted as ‘home delivery’ and ‘institutional delivery’. Objective: The objective of this study is to analyze factors associated with the utilization of health institute as delivery and estimate the probabilities of institutional delivery using some selected independent variables. Materials and Methods: Data used were extracted from individual recode of a data file of Nepal Demography Health Survey (NDHS) 2006 and 2011. The unit of analysis for this study is Ever Married Women (EMW) who had at least one live birth in the five years preceding the survey. Sample of this study consists of 4182 EMW for 2006 NDHS and 4079 EMW for 2011 NDHS. The dependent variable is place of delivery. The independent variables are mixture of categorical and continuous variables. For building of suitable statistical models, various types of models were explored and different measure of models adequacy test were applied. Finally, two logistic regression models were developed separately for 2006 and 2011 NDHS data. Results: Fitted model showed several variables: education level, wealth index, birth order, residence and ANC by provider were highly significant predictors for the selection of place of delivery for 2006 NDHS but in 2011 NDHS age was also highly significant. Goodness of fit tests (Hosmer-Lemeshow chi-square statistic), multicollinearity diagnostics, residual analysis and outliers (leverage value) showed that both models fit well to the proposed logistic regression model. Conclusion: A Comparative assessment of model coefficients between 2006 and 2011 NDHS, it is found that the values are only slightly different for most of the predictors under consideration demonstrating consistency of associations found in the two surveys. Nepalese Journal of Statistics, 2017, Vol. 1, 55-72